An integrated analytical framework for carbon dioxide emission reduction potential in the water production and supply industry in China - Jiang, Guodong; Zuo, Qiting; Ma, Junxia; Zhang, Zhizhuo; Zhao, Chenguang (Scientific reports, 2025)
The Water Production and Supply (WP&S) industry faces the dual objectives of ensuring water supply security and achieving carbon neutrality. An integrated analytical framework (Measurement-Assessment-Identification) was developed to measure carbon dioxide emissions from the WP&S industry (WP&S-CO 2 emissions), assess the CO 2 emissions reduction potential of the WP&S industry (WP&S-CRP), and identify the key driving forces of WP&S-CRP. In the measurement module, a method for measuring CO 2 emissions specific to the WP&S industry is proposed. In the assessment module, we clarify the concept of CO 2 emissions reduction potential within the WP&S industry and develop a corresponding assessment model. In the identification module, a multiple model for identifying the driving factors of WP&S-CRP is constructed. This framework is applied to a long-term case study across various provinces and regions in China. The results indicate that: (1) Since 2010, China’s WP&S-CO 2 emissions have experienced fluctuating growth, with a spatial distribution pattern that decreases from coastal to inland areas. The WP&S industry in the North coast and Guangdong Province showed the highest emissions on two spatial scales, respectively. (2) Against the backdrop of an increasing total water supply, the WP&S-CRP of China decreased from 0.75 in 2010 to 0.38 in 2022, indicating a gradual improvement in green production levels within the industry. However, regions such as the Northeast, Middle Yellow River, and provinces like Hebei and Heilongjiang still exhibit high levels of WP&S-CRP. (3) The water for production and operation and the pipe network density are the most significant positive and negative driving forces for WP&S-CRP, respectively. This study offers potential references for developing sustainable development strategies for the WP&S industry in various provinces of China with the goal of carbon neutrality.